Household energy use and barriers in clean transition in the Tibetan Plateau - Ran Xing; Yaojie Li; Zhihan Luo; Rui Xiong; Jiaqi Liu; Ke Jiang; Yatai Men; Huizhong Shen; Guofeng Shen; Shu Tao (Resources, Environment and Sustainability)
The inefficient combustion of traditional biomass fuels in the Tibetan Plateau, the world’s highest region, impacts both local ecosystems and global climate change despite the substantial renewable energy potential and ongoing economic growth of the area. However, the utilization of clean household energy sources and the enablers supporting their sustained use in this region remain underexplored. Through the regional household survey and fuel-weighing campaign, we observed that clean modern energy sources, such as gas and electricity, were used for over 85% of the year in urban areas but only 25% in rural areas. Approximately 3.98 million residents still predominantly rely on traditional solid fuels for daily cooking and/or heating. A substantial energy inequality was identified, with Gini coefficients of 0.65 and 0.55 for cooking and heating, respectively. Despite the disparity in clean energy adoption across income groups being relatively small, the regional utilization of clean energy is severely constrained by limited accessibility and affordability. This has minimized the impact of household characteristics, such as gender, age, and education level, and diminished the effect of rising incomes on accelerating clean cooking practices. The findings highlight the urgent need for targeted residential energy interventions and incentives to promote a clean energy transition in the Tibetan Plateau, as achieving universal clean energy access by 2030 is unlikely without significant efforts.